Development of a secure, standardised and interoperable surveillance platform for race-related injury and illness data within the UCI men`s and women`s road cycling world tour: a study protocol - Fallon, T.; Decorte, R.; Verstockt, S.; Palmer, D.; Bigard, X.; Heron, N. (BMJ Open Sport & Exercise Medicine, 2026)
Background Professional road cycling is associated with a high incidence of traumatic injuries. Despite these risks, current injury data-collection methods lack consistency and standardisation, thereby limiting meaningful surveillance and prevention efforts.